Asthma Exacerbation Triggered by Wildfire: A Standardized Patient Case to Integrate Climate Change Into Medical Curricula - Japhia Ramkumar; Holly Rosencranz; Leslie Herzog (Association of American Medical Colleges, 2021)
Introduction Climate change presents unprecedented health threats. It is imperative that medical trainees understand the implications of climate change/planetary health on the physical and mental health and well-being of their patients. Medical professionals generally are not trained to consider climate change impacts in patient encounters. Hence, there is a need to train climate-aware providers who will be at the forefront of patient care in managing these current and emerging health impacts. Methods We created a standardized patient (SP) case enhanced with details of risks and health impacts due to exposure to wildfire smoke. This session was deployed to 11 internal medicine clerkship students as part of a standard OSCE already included in our curriculum to evaluate core clinical and communication skills. Two cohorts, a group activity, and a one-on-one encounter were deployed and followed with a faculty debrief and learner assessments. Results Students had increased awareness and knowledge of health impacts of climate change and potential actions for adaptation and mitigation. The improvements were statistically significant for the one-on-one cohort (p = .006). Postsimulation comments were favorable; students were more inclined to consider health impacts, risks, and vulnerabilities exacerbated by climate change. Discussion Students had an increased recognition of climate change as a force impacting their patients' health which should be considered in patient care. This format allowed retention of well established curricular content, but also the inclusion of other crucial emerging issues that will impact public health locally and globally and foster the development of climate-aware health care providers.